The Influence Of Organizational Citizenship Behavior (Ocb) And Work Motivation On Employee Performance In Seluma Regency Regional Financial Board - Lilis Syahfitri; Sulisti Afriani; Rinto Noviantoro (Universitas Dehasen Bengkulu, 2023)
The success of an organization is strongly affected by the performance of thecompany or individual employees. Every organization is always trying to improve employee performance to achieve the goals set. Performance is still a problem that is always faced by management, so management needs to know the factors that affect the performance of these employees. This study aims to determine the effect of Organizational Citizenship Behavior (OCB) and work motivation on employee performance in the Regional Financial Agency of Seluma Regency. The samples in this study were 30 employees the Regional Financial Agency of Seluma Regency who had become State Civil Apparatuses (ASN). Data collection using a questionnaire and the method of analysis used is multiple linear regression, determination test and hypothesis testing. Organizational Citizenship Behavior (OCB) has a significant influence on employee performance in the Regional Financial Agency of Seluma Regency. This illustrates that the increasing Organizational Citizenship Behavior (OCB) style of the head of the Regional Financial Agency of Seluma Regency, the employee's performance will also increase. Motivation has a significant influence on employee performance at the in the Regional Financial Agency of Seluma Regency. This illustrates that the increasing work of employees, the performance of employees of in the Regional Financial Agency of Seluma Regency will also increase. Simultaneously the Organizational Citizenship Behavior (OCB) variables and motivation have a joint influence on employee performance in the Regional Financial Agency of Seluma Regency.